2023
DOI: 10.1002/adfm.202302045
|View full text |Cite
|
Sign up to set email alerts
|

V Doping in NASICON‐Structured Na3MnTi(PO4)3 Enables High‐Energy and Stable Sodium Storage

Abstract: NASICON‐structured Na3MnTi(PO4)3 represents an appealing cathode for sodium storage. However, the low potential from Ti3+/4+ redox pair (≈2.1 V versus Na+/Na), undesirable rate capability, and unfavorable cyclability have inhibited its practical application. Herein, this study designs a Na3.1MnTi0.9V0.1(PO4)3 (NMTVP) cathode material by doping V into the Na3MnTi(PO4)3. The V substitution not only increases the medium discharge voltage, but also increases the capacity. The as‐prepared NMTVP demonstrates a four‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…Based on a first discharge capacity of 160 mA h g −1 and an average discharge potential of 2.8 V, the energy density of NCFVP reaches ∼450 W h kg −1 , which exceeds most phosphate/pyrophosphate-based SIB cathode materials. 10,32,41–47…”
Section: Resultsmentioning
confidence: 99%
“…Based on a first discharge capacity of 160 mA h g −1 and an average discharge potential of 2.8 V, the energy density of NCFVP reaches ∼450 W h kg −1 , which exceeds most phosphate/pyrophosphate-based SIB cathode materials. 10,32,41–47…”
Section: Resultsmentioning
confidence: 99%
“…3j. Compared to state-of-the-art Mn-based cathodes, 15,57–62 the current Na-deficient material presents a competitive energy density and remarkable cycling stability with a decent production cost, as seen in Fig. 3k, l and Table S7 †…”
Section: Resultsmentioning
confidence: 99%
“…The low cost, high stability, and wide distribution of feedstock costs offered by sodium-ion batteries (SIBs) make them well-suited for fulfilling the demands of large-scale electrochemical energy storage systems. However, SIBs still have great challenges; despite having the same working principle as lithium-ion batteries (LIBs), they are limited by the ionic radius (Na + : 1.02 Å; Li + : 0.76 Å), which leads to poor de-embedding capability. Therefore, there is a need to develop more suitable electrode materials to fulfill large-scale storage requirements. In recent years, there has been a progression in sodium-ion cathode materials, with the emergence of various materials including transition-metal oxides, polyanion materials, and Prussian analogues. Iron-based polyanion materials with low raw material cost, high thermal stability, and environmental friendliness have gained a lot of attention for their advantages. Na 4 Fe 3 (PO 4 ) 2 P 2 O 7 (NFPP, theoretical capacity: 129 mA h g –1 ) was connected by combining [PO 4 ] and [P 2 O 7 ] groups with [FeO 6 ] octahedra, based on the redox Fe 2+ /Fe 3+ (average working voltage: 3.1 V), to realize the de-embedding of Na + in the cathode. Kim et al reported NFPP as a sodium-ion cathode material with a high reversible capacity of 113.5 mA h g –1 , marking the first discovery of such quality.…”
Section: Introductionmentioning
confidence: 99%